OPTIMIZATION OF DRINKING WATER DISTRIBUTION NETWORK OF TIRTA MEDAL REGIONAL PUBLIC DRINKING WATER COMPANY NORTH SUMEDANG BRANCH - Ilhamudin H, Aldiansyah
The piped network in the service of Perumda Air Minum Tirta Medal, North Branch, is currently only 11.35%. To achieve the 80% target, set by the RISPAM Kabupaten Sumedang 2040, Perumda Air Minum Tirta Medal plans to obtain new raw water sources for the next 18 years (until 2040). To support this, it is necessary to have a distribution network that meets the standards. The planning phase begins with identifying goals, collecting primary and secondary data, conducting literature studies, projecting water needs, designing three alternative networks, selecting the best alternative route, and creating technical drawings. The service area covers Sumedang Utara Subdistrict, which consists of 9 villages and 4 urban villages, part of Cimalaka Subdistrict, which consists of 3 villages, and part of Cisarua Subdistrict, which consists of 1 village. In the final year of the planning period, which is 2040, the projected water needs planned to serve the planning area are 338.182 liters/second. Three alternative drinking water distribution networks were created with various route options. The best alternative was selected using the Simple Additive Weighting (SAW) method based on financial-economic, technical, public health, environmental, and socio-economic criteria. The assessment results showed that the selected alternative is alternative 1. The distribution network is designed with combined flow and combined network patterns, with a total planned pipe length of 37,382 meters. District Metered Area (DMA) is designed by forming six DMA zones, which are planned to reduce water losses in the drinking water distribution system in the North Branch of Sumedang to 20% by 2040. The financial evaluation using Net Present Value and Benefit Cost Ratio indicates that the planning is financially feasible.